Guía de aves de la parroquia de Zumbahua. - Cuchipe Ramírez, Pablo Giovanny (2021)
This research project aimed to prepare a bird guide for the Zumbahua parish; It used different methods and techniques to elaborate the guide and an environmental diagnosis of the site. It allowed identifying the Parish's current state and determine the places where the inventory would be carried out. Different sources were reviewed to make the diagnosis through bibliographic research and site visits. An inventory of birds was made through field trips. Intensive search and direct observation were applied through marked trails and roads in each study area. It was possible to identify 19 species of birds in the open field and two species symbols that the locals tell in their legends. A field sheet was filled out with the main characteristics of the birds. It made a file of Order, Family, Scientific Name, Common Name, Local Name, English Name, Reference, space for the photo, State of Conservation, a brief description, the location by Provinces, and natural regions. As a final result, a Bird Guide was obtained with 21 species, an essential tool for the community and effective use and importance for tourists, tourism and environment students, ecologists, ornithologists, and other people dedicated to bird watching. For this reason, this work has significant environmental, social and economic value for the direct and indirect beneficiaries of the Parish. This work also aims to generate awareness in the care of the environment and protect each of the species that inhabit the Parish. It is essential that all those involved directly and indirectly, with the authorities' help, know about birding tourism, hold talks and training to create an Environmental Awareness, and make Zumbahua a privileged place for bird watching.